Identification Of Counterfeit Antibiotics: Approaches And Results Of Analysis (Texas Journal of Medical Science, 2025)
Counterfeiting of medicines (MP) is a problem that has accompanied humanity throughout its history [1]. However, special attention was drawn to it only in the 20th century, in particular, since the mid-1980s. In 1985, this issue was officially raised at an international conference of experts on the rational use of medicines, organized under the auspices of the World Health Organization (WHO).